Giardia and Cryptosporidium in resident wildlife species in Arctic Alaska - Caroline Van Hemert; Lora R. Ballweber; David R. Sinnett; Todd C. Atwood; Anthony Fischbach; David D. Gustine; Kristy L. Pabilonia (Food and Waterborne Parasitology, 2023)
Giardia and Cryptosporidium are zoonotic protozoan parasites that can infect humans and other taxa, including wildlife, often causing gastrointestinal illness. Both have been identified as One Health priorities in the Arctic, where climate change is expected to influence the distribution of many wildlife and zoonotic diseases, but little is known about their prevalence in local wildlife. To help fill information gaps, we collected fecal samples from four wildlife species that occur seasonally on the northern Alaska coastline or in nearshore marine waters—Arctic fox (Vulpes lagopus), polar bear (Ursus maritimus), Pacific walrus (Odobenus rosmarus divergens), and caribou (Rangifer tarandus)—and used immunofluorescence assays to screen for Giardia cysts and Cryptosporidium oocysts. We detected Giardia cysts in 18.3% and Cryptosporidium oocysts in 16.5% of Arctic foxes (n = 109), suggesting that foxes may be potentially important hosts in this region. We also detected Giardia cysts in a single polar bear (12.5%; n = 8), which to our knowledge represents the first such report for this species. Neither parasite was detected in walruses or caribou.